2012
DOI: 10.1097/opx.0b013e318240488e
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Face Processing in Early Monocular Deprivation from Enucleation

Abstract: These results indicate an impairment in the feature spacing and feature aspects of face perception with ME. They also suggest a present yet, incomplete, development of holistic face processing in this group. Although the complete removal of inhibitory binocular interactions and/or the absence of binocular competition in early ME may result in cortical reorganization of the visual system and preserve low- to mid-level spatial vision, it may be insufficient for the maturation of high-level face perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…In contrast to people with amblyopia (Barrett, Bradley, & McGraw, 2004;Birch, 2013;Kiorpes, 2006;Levi, 2006;McKee, Levi, & Movshon, 2003;Wong, 2012), enucleated observers exhibit intact or enhanced spatial vision (Kelly, Moro, & Steeves, 2013;Steeves, González, & Steinbach, 2008;Steinbach & González, 2006), particularly at low contrast Nicholas, Heywood, & Cowey, 1996;Steeves et al, 2004). In common with, although not as severely as in people with amblyopia, enucleated observers also exhibit deficits in face (Kelly, Gallie, & Steeves, 2012) and in motion perception Steeves et al, 2002). The dissociation between spatial and motion perception is illustrated by the deficits in speed discrimination but not in luminance contrast perception shown by enucleated observers .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast to people with amblyopia (Barrett, Bradley, & McGraw, 2004;Birch, 2013;Kiorpes, 2006;Levi, 2006;McKee, Levi, & Movshon, 2003;Wong, 2012), enucleated observers exhibit intact or enhanced spatial vision (Kelly, Moro, & Steeves, 2013;Steeves, González, & Steinbach, 2008;Steinbach & González, 2006), particularly at low contrast Nicholas, Heywood, & Cowey, 1996;Steeves et al, 2004). In common with, although not as severely as in people with amblyopia, enucleated observers also exhibit deficits in face (Kelly, Gallie, & Steeves, 2012) and in motion perception Steeves et al, 2002). The dissociation between spatial and motion perception is illustrated by the deficits in speed discrimination but not in luminance contrast perception shown by enucleated observers .…”
Section: Introductionmentioning
confidence: 77%
“…The failure to replicate the naso-temporal and upper/lower hemifield asymmetries in motion perception that are sometimes (Bowns, Kirshner, & Steinbach, 1994;Reed et al, 1991), but not always (Kelly, Gallie, & Steeves, 2012), found in enucleated observers may be due to differences in age at enucleation (AAE) in the different studies. Because it takes approximately 6 months for central vision to be obstructed by an intraocular tumor, some of our participants may have experienced a period of binocular vision.…”
Section: Motion Perceptionmentioning
confidence: 93%
“…As well, given the relative lateralization of many face processes, interhemispheric communication can be necessary for efficient functioning [Mohr et al, ]. The significant bidirectional reduction in FA in the interhemispheric V1 projections of ME participants may therefore contribute to the slower response latencies and impaired holistic face processing reported in this group [Kelly et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mild impairments for visual motion perception and oculomotor abilities are observed [for review, see Kelly et al, ; Steeves et al, ]. On tasks requiring participants to process the shape and spacing of internal facial features, individuals who have undergone early monocular enucleation also demonstrate mild impairments compared to both monocular and binocular viewing controls [Kelly et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Enucleation, however, seems to have adverse effects on the maturation of functions, such as motion [9][10][11] and face perception. 12 When evaluating the characteristics of monocular vision, the question arises as to the contribution of oculomotor control to the visual functions investigated. To this day, however, only fixation stability and optokinetic nystagmus (OKN) have been measured in one-eyed observers to our knowledge.…”
mentioning
confidence: 99%